Digital capitalism and young people's work patterns: The dynamics of side jobs among Indonesia's gen Z - Rahma Kun Zakiyah; Sirajul Arifin; Luthfi Akmal Muzakki (Nur Science Institute, 2026)
This study investigates the contradictions of side jobs and the gig economy among Generation Z in Indonesia. Although this sector is considered to offer flexibility, independence, and diverse career development opportunities, the reality in the world of work shows tension between expectations of freedom and unstable working conditions. This study applies a qualitative approach with a systematic literature review design. Data was obtained through the synthesis of accredited journal articles and reports from reliable research institutions published between 2020 and 2024. Data analysis was conducted using thematic analysis methods to identify patterns of experience and structural contradictions that have been noted in the literature. The findings show that the promised flexibility and autonomy are often illusory. Fluctuating income, lack of social security, and dependence on non-transparent platform algorithms create a situation of “pseudo-autonomy.” These conditions lead to economic vulnerability and psychosocial pressures, such as anxiety, stress, and feelings of alienation due to prolonged job uncertainty. These results confirm that the welfare of Gen-Z gig workers needs to be evaluated from various dimensions, not only based on income but also psychological and social aspects.